2022
DOI: 10.3390/ijerph19021018
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Symptoms of Anxiety, Depression, and Insomnia in Spain in the COVID-19 Crisis

Abstract: Background: General population, frontline healthcare workers (HCWs), and adult students in Spain are at risk of anxiety, depression, and insomnia symptoms during the COVID-19 crisis. A meta-analysis of the individual studies on these symptoms would provide systematic evidence to aid policymakers and researchers in focusing on prevalence, risk, and best interventions. Objective: This paper aims to be the first meta-analysis and systematic review to calculate the prevalence of anxiety, depression, and insomnia s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 66 publications
1
36
2
1
Order By: Relevance
“…In a systematic review with meta-analysis, Chen et al reported the overall prevalence of mental health disorders in front-line HCWs, general HCWs, and the general population in African countries as 49%, 36%, and 38%, respectively [ 66 ]. Another review revealed an overall prevalence of mental illness symptoms in front-line HCWs and the general population in Spain of 42% and 19%, respectively [ 68 ]. The pooled prevalence of psychological distress and burnout reported by Batra et al was 46.1% and 37.4% among HCWs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review with meta-analysis, Chen et al reported the overall prevalence of mental health disorders in front-line HCWs, general HCWs, and the general population in African countries as 49%, 36%, and 38%, respectively [ 66 ]. Another review revealed an overall prevalence of mental illness symptoms in front-line HCWs and the general population in Spain of 42% and 19%, respectively [ 68 ]. The pooled prevalence of psychological distress and burnout reported by Batra et al was 46.1% and 37.4% among HCWs [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, future research is encouraged to research the fear of failure and the IP model by considering the COVID-19 phenomenon. COVID-19 has been last for 2 years which is associated with businesses risks ( Yue et al, 2020 ; Li et al, 2021 ) and mental health symptoms, i.e., a high prevalence of anxiety, depression, and insomnia ( Chen et al, 2021 ; Pappa et al, 2021 ; Zhang et al, 2022 ). Although COVID-19 has reached researchers’ attention on IB policy ( Van Assche and Lundan, 2020 ) and strategy ( Verbeke and Yuan, 2021 ), there is no IB empirical research that explored the fear of failure.…”
Section: Implication For Future Researchmentioning
confidence: 99%
“…Globalisation of the world economy has created international opportunities. Nevertheless, taking the current international business (IB) environment into consideration, the global infection status of Coronavirus Disease-19 (COVID-19) had brought risks on economic activities ( Yue et al, 2020 ) and mental health disorders to individuals ( Chen et al, 2021 ; Pappa et al, 2021 ; Zhang et al, 2022 ). Internationalisation is instrumental to a firm’s survival and growth along with the potential for a positive effect on economic development ( The World Bank, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the COVID-19 pandemic has led to an increase in stress, anxiety, depression, and sleep disturbances in many regions of the world (Halsøy, Johnson, Hoffart, & Ebrahimi, 2021; Zhang et al, 2022). The purpose of our study is to describe the regional variation and the development of the longitudinal relationships between sleep and mental health as well as between sleep, mental health, and the incidence of COVID-19 in Sweden over a 14-month period of the pandemic using a set of different analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the COVID-19 pandemic has led to an increase in stress, anxiety, depression, and sleep disturbances in many regions of the world (Halsøy, Johnson, Hoffart, & Ebrahimi, 2021;Zhang et al, 2022).…”
mentioning
confidence: 99%